Exploring impacts of computer aided learning (CAL) on english language teaching in secondary schools in class ix-x in rural areas in Bangladesh - Jhumu, Rawnak Jahan (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2015.